Bioarchaeology : an introduction to the archaeology and anthropology of the dead - Sutton, Mark Q. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Bioarchaeology covers the history and general theory of the field plus the recovery and laboratory treatment of human remains. Bioarchaeology is the study of human remains in context from an archaeological and anthropological perspective. The book explores, through numerous case studies, how a society deals with their dead can reveal a great deal about that society, including religion, political, economic, and social organizations. It details recovery methods and how, once recovered, human remains can be analysed to reveal details about the funerary system of the subject society and inform on a variety of other issues, such as health, demography, disease, workloads, mobility, sex and gender, and migration. Finally, the book highlights how bioarchaeological techniques can be used in contemporary forensic settings and in the investigations of genocide and war crimes. In Bioarchaeology, theories, principles and scientific techniques are laid out in a clear, understandable way and students of archaeology at undergraduate and graduate levels will find this an excellent guide to the field."--
The Discipline of Bioarchaeology -- Discovery and Recovery -- In the Laboratory: Description and Basic Analysis of Human Remains -- Treating the Dead: The Funerary System -- Paleopathology I: Metabolic, Nutritional, and Occupational Stress -- Paleopathology II: Disease and Abnormalities -- Trama -- Specialized Studies -- Interpretive Theory and Data Integration -- Lives Once Lived: The Anthropology of the Dead -- Contemporary Application: Forensic Anthropology.
OCLC-licensed vendor bibliographic record.
Keywords: Human remains (Archaeology); Human skeleton -- Analysis; SOCIAL SCIENCE / Archaeology